Pengaruh Good Corporate Governance Dan Firm Size Terhadap Profitabilitas (Studi Empiris Pada Perusahaan Non Keuangan Indeks LQ 45 Yang Terdaftar Di BEI Tahun 2013-2017): Effect of Good Corporate Governance and Firm Size on Profitability (Empirical Study on Non-Financial Companies LQ 45 Index Listed on the IDX in 2013-2017) - Suroto, Faisal; Setiadi, Iwan (Universitas Muhammadiyah Sidoarjo, 2019)
This study aims to determine the effect of Good Corporate Governance on profitability and company size. Good corporate governance in this study is proxied by independent board of commissioners, managerial ownership, institutional ownership, audit quality and Firm Size. Company profitability is measured by Return on Equity (ROE). This type of research is quantitative with a descriptive approach. The population in this study is the LQ45 non-financial company listed on the Indonesia Stock Exchange in 2013-2017. The sample selection technique is using purposive sampling. The type of data used is student data. The data analysis technique in this study used multiple linear regression analysis. The results of this study indicate that simultaneous independent commissioner variables, managerial ownership, institutional ownership, audit quality and firm size have a significant effect on profitability. partially independent board of commissioner variables have a significant negative effect on priofitability. Managerial ownership does not have a significant effect on profitability. Institutional ownership has a significant positive effect on profitability. Audit quality does not have a significant effect on profitability, Firm size does not have a significant effect on profitability.